Revelando saberes ambientais de professoras ribeirinhas (Pantanal de Cáceres – MT) - Minervini, José Márcio Miranda (2007)
This study is the result of the challenge of resources provided by the Oral History Method, which we used for the building of new knowledge, supported by new methodological approaches, gathering systematic reflective and critical procedures, allowing greater safety and saving in the range of valid knowledge and true. This is a qualitative research, based on the Oral History of Life and constructed from open oral interviews, provided by the retired teachers of the elementary schools of the municipal school of Cáceres, the locations of Caiçara, Porto Limão and João José: Emídia de Souza Pinheiro, Feliciana Torres Cunha, Severiana Soares de Oliveira, respectively. Aiming the opportunity to get a cutting of the environmental reality of the locus of research, detecting teaching indicators for the work with the Environmental Education, as a reflection of individual actions lived and experienced by these teachers at school, and the possibility of an even higher understanding in the field of education and the environment for other research. The choice of collaborating teachers was due to the age criterion and the location of schools in different strategic points of the wetlands. The interviews were conducted after several meetings with teachers, tape-recorded and subsequently implemented in the form of texts. It is a record of experiences as riparian teachers, with the intention to know their life trajectories and revealing as a source of environmental knowledge. This research aims to offer the academy a reflection on the value of methodological techniques based on orality to be used as another brick in the wall construction of science. A proposal that opens the way for new approaches and discovery of new facts or data in various areas of knowledge, especially those related to environmental issues.